1973
DOI: 10.1051/forest/19730203
|View full text |Cite
|
Sign up to set email alerts
|

Étude des gelées tardives en relation avec les problèmes de reboisement

Abstract: RÉSUMÉLes gelées tardives constituent dans certains cas un handicap important pour le reboiseur. Les

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…Ic), depending on frost damage intensity on the terminal shoot (Contingency table 3 × 2). Details of calculating risk of fork emergence for the "frost-nipped shoot" damage level, and relative risk of fork emergence for the "frost-nipped shoot" damage level relative to the "undamaged" level are provided in Table Ia plant), as well as the air cooling dynamics, the height reached by the plant and its phenology [4], it would be especially necessary to acquire as much information as possible on the phenology which varied widely from one individual to another. In the lack of such a statistical model, the consequences of frost on the emergence of fork, even if the frost was well defined, could not be estimated accurately without knowing the immediate damage it had caused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ic), depending on frost damage intensity on the terminal shoot (Contingency table 3 × 2). Details of calculating risk of fork emergence for the "frost-nipped shoot" damage level, and relative risk of fork emergence for the "frost-nipped shoot" damage level relative to the "undamaged" level are provided in Table Ia plant), as well as the air cooling dynamics, the height reached by the plant and its phenology [4], it would be especially necessary to acquire as much information as possible on the phenology which varied widely from one individual to another. In the lack of such a statistical model, the consequences of frost on the emergence of fork, even if the frost was well defined, could not be estimated accurately without knowing the immediate damage it had caused.…”
Section: Discussionmentioning
confidence: 99%
“…The forester should pay great attention during this critical phase of the formation of high quality butt-log wood, in areas where the forest stand is particularly sensitive to frost. In zones with high frost risk, it is recommended that silvicultural techniques to reduce this risk should be used preventatively, for instance, the maintenance of lateral forest shelter [2,4] or curative measures to reduce its impact by rational fork pruning [1,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…But cover provided by understorey also has a positive effect beyond browsing pressure. The understorey reduces the risk of spring frosts which affect fir more than spruce [1,3,50] and protects seedlings from over-exposure to sun and uprooting when soil is washed away during strong rains, two important causes of fir mortality [56]. In addition, by creating shade, understorey limits the development of herbaceous species such as Festuca altissima that may hinder fir establishment through allelopathic processes [5].…”
Section: How Fir May Be Replaced By Spruce or Notmentioning
confidence: 99%
“…The extent of damage due to late frost depends on the species, the provenance, the lowest temperature reached and the phenological stage of the plant when frost occurred [4,29]. Day and Pearce [14] reported that oak is more sensitive to late frost than ash and beech.…”
mentioning
confidence: 99%
“…B) On the GU established at the end of the previous growing season: a subterminal bud (STB-pGU) (4) and a lateral bud (LB-pGU) (5).…”
mentioning
confidence: 99%